Fatigue and its associated factors in liver transplant recipients in Beijing: a cross-sectional study. Issue 2 (23rd February 2017) - Lin, Xiao-Hong; Teng, Sha; Wang, Lu; Zhang, Jing; Shang, Ya-Bin; Liu, Hong-Xia; Zang, Yun-Jin
Abstract : Objectives: Fatigue is a highly prevalent symptom experienced by patients who underwent the liver transplantation. However, the influencing factors of fatigue are poorly understood by healthcare professionals. The aim of this study was to examine the intensity, interference, duration and prevalence of fatigue in liver transplantation recipients and to explore the influencing factors of post-transplantation fatigue. Design: A cross-sectional design was used in this study. Methods: A convenience sample of liver transplant recipients was recruited at an outpatient transplant clinic of a general hospital in Beijing, China. Self-report survey data were provided by liver transplant recipients using the Fatigue Symptom Inventory (FSI), the Hospital Anxiety and Depression Scale (HADS), the Perceived Social Support Scale (PSSS) and the Athens Insomnia Scale (AIS). Demographic, clinical and psychosocial parameters were evaluated as fatigue influencing factors. Results: Participants (n=285) included 69 women and 216 men. Fatigue was found in 87.0% of liver transplant recipients. Mean scores of fatigue intensity items were 4.47±2.85, 1.93±1.97, 3.15±2.13 and 2.73±2.42 (most fatigue, least fatigue, average fatigue in the week prior to assessment and fatigue at the point of assessment). The mean score of fatigue interference was 2.27±2.09.The number of days fatigued in the week prior to assessment was 2.26±2.02 and the amount of time fatigued each day was 2.75±2.44. Spearman's correlation analysis showed that fatigue intensity was positively associated with anxiety, depression and insomnia (p<0.001 for all), while fatigue interference was positively associated with gender, anxiety, depression and insomnia (p<0.05 for all). In the multiple linear regression analysis, anxiety and insomnia were positively associated with fatigue intensity (p<0.001), and insomnia, depression and anxiety were positively associated with fatigue interference (p<0.001). Conclusions: Fatigue is common in liver transplant recipients, and it is strongly associated with insomnia, anxiety and depression.